1999
DOI: 10.1093/sw/44.5.416
|View full text |Cite
|
Sign up to set email alerts
|

Social Consequences of Malnutrition

Abstract: Each year millions of people die from malnutrition-related problems. Those who survive are robbed of a healthy body, a sound intellect, and the hope for healthful living. Despite its global toll malnutrition is given limited attention by the world community; hence, it is generally viewed as a silent emergency by advocacy organizations. The causes and consequences of malnutrition are complex, and it will require the concerted efforts of all social institutions, including the social work profession, to combat ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 5 publications
0
8
0
1
Order By: Relevance
“…In discussing the relationship between malnutrition and social work, Seipel (1999) succinctly and articulately suggests several roles that social workers may play in combating malnutrition:…”
Section: People In Less Developed Countriesmentioning
confidence: 99%
See 2 more Smart Citations
“…In discussing the relationship between malnutrition and social work, Seipel (1999) succinctly and articulately suggests several roles that social workers may play in combating malnutrition:…”
Section: People In Less Developed Countriesmentioning
confidence: 99%
“…While Seipel (1999) argues that poverty reduction is the most important step in ensuring that people receive adequate nutrition, he also argues that the two are not inextricably linked and a human right that must be explicitly protected is the right to sufficient food. An example of this occurring is the United Nations Convention on the Rights of the Child (1990) which in article 24 protects the rights of children to 'safe drinking water [and] nutritious food' and article 27, which states that 'governments should help families and guardians who are not able to provide this [food]'.…”
Section: Promoting the Right To Good Nutrition As A Basic Right Rathementioning
confidence: 99%
See 1 more Smart Citation
“…Unlike malnutrition that characterizes underdeveloped countries (Seipel 1999), food insecurity does not endanger life, but has pervasive effects on health. It is linked to dietary intake, nutritional status, and ultimately to physical health outcomes like child growth morbidity and mortality (Wolfe and Frongillo 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Despite strong growth in global food production, sub-Saharan Africa is the only region in the world where the number of hungry people has risen over 19% during the last decade (USDA Agriculture and Trade Reports, 2006). Seipel (1999) reported that the per capita food supply for direct human consumption in sub-Saharan Africa decreased with 252 kJ/day from 1960 to 1992, while the Northern Africa, East Asia, South Asia and Latin America all reported an increase in food supply (FAO, 1996). Furthermore only in sub-Saharan Africa there was a recorded increase in undernourished people, compared to other developing countries which all reported a decrease (FAO, 1996).…”
Section: Introductionmentioning
confidence: 99%